О роли музыки в жизни варваров и греков, обитавших в древности на территории Северного Причерноморья - Вдовиченко, И.И.; Хлебко, Н.Н. (Культура народов Причерноморья, 2003)
This article explains the role of musical instruments in the myths and ordinary life of the ancient population of Black Sea Coast region.